Investigation of the effects of orientation and window usage on external walls in terms of heating and cooling energy - Bektaş Ekici, Betül; Aksoy, U. Teoman (My University, 2008)
This study investigated effective ways of minimizing the amount of energy used for heating and cooling caused by windows in the building envelope. The use of glass material in windows is discussed in terms of reducing heating and cooling energy consumption. The hourly total heating and cooling energy calculations were carried out for the 1st, 11th, and 21st days of each month using the previous 10-year period's meteorological data for Elaz??. Energy loads of windows were estimated using a computer program written in MATLAB. Energy requirements of different among different alternatives. In conclusion, OR1/1 (square formed) buildings have the minimum heating and cooling requirements. Among 5 different glass alternatives, xenon filled double glass units require 33%-82% less heating and cooling energy than the others. © TÜBITAK.
Keywords: Double-glass; Energy conservation; Heating and cooling energy requirements; Windows